Targeting SHIP1 for therapeutic intervention in Alzheimer's disease: Nonhuman/Target identification and validation studies: Inflammation and innate immunity. (7th December 2020) - Obst, Juliane; Bradshaw, William; Roberts, Hazel Hall; Priestley, Richard; Jimenez‐Antunez, Carmen; Cowley, Sally A.; Gileadi, Opher; Mead, Emma; Daniel, Elena Di; Davis, John B.
Abstract: Background: Genome wide association studies (GWAS) and systems biology approaches have identified several Alzheimer's disease (AD) risk associated genes expressed in microglia. SHIP1, an inositol phosphatase, has been identified as a regulator of TREM2 signalling, inhibiting the cascade by opposing SYK and PI3K phosphorylation. A SHIP1 variant (rs39349669) confers AD risk by increasing SHIP1 expression, thereby inhibiting TREM2 signalling and reducing beneficial microglial phenotypes including phagocytosis. We hypothesise that SHIP1 inhibition may restore the protective signalling pathway associated with TREM2. Method: Utilising human iPSC macrophages, we aim to understand the role of SHIP1 in regulating TREM2 signalling. We are able to stimulate TREM2 signalling using an activating antibody, and we have measured SYK phosphorylation and Ca 2+ flux in the presence of SHIP1 modulators. As development of small‐molecule inhibitors of phosphatases is challenging due to polar active sites, we hope to identify allosteric binding sites on SHIP1. We have determined the structure of SHIP1 and aim to use crystallography to promote the development of potent modulators. We have performed a crystallographic fragment screen of 597 compounds to identify SHIP1 binders, which will be used as starting points for medicinal chemistry. Result: The SHIP1 inhibitor 3AC increases SYK phosphorylation and intracellular Ca 2+ flux following TREM2 stimulation. We are now working with an isogenic SHIP1 KO iPSC line to validate these findings. We have determined the structure of the phosphatase and C2 domains of SHIP1, both in the apo form and with a phosphate and a magnesium ion bound to the active site. We are working towards further structures. The fragment screen revealed more than 100 binding events. These identify new potential binding pockets outside of the active site and work is ongoing to perform SAR. Conclusion: We have demonstrated that SHIP1 regulates TREM2 signalling and is a druggable target. Furthermore, we are working towards identifying inhibitors that will increase TREM2 mediated protective signalling in microglia. We have improved understanding of the structural basis of the reaction catalysed by SHIP1, which will inform the development of novel and selective compounds. Targeting SHIP1 could represent a novel therapeutic strategy for the treatment of AD.